ACCESSORY IRON MINERALS IN IMPACTITES OF THE KARA ASTROBLEME, PAY KHOY RANGE - Fel'dman V.I.; Sazonova L.V.; Guzhova A.V. (My University, 1988)
While examining thin sections of tagamite and suevite from the Kara astrobleme with the Camebax electron microprobe and the Camscan scanning electron microscope, the authors identified and studied native iron, pyrrhotite and pyrite. In tagamite (Anaroga River), these minerals are present as irregular microsegregations, uniformly scattered in the rock matrix and ranging in size from several to tens of micrometers. In suevite (Mareygo Landmark), only pyrrhotite was recorded, as clusters of spherical segregations, extending along flow lines in glass in discontinuous strips. The total content of accessory ore minerals in our samples rarely exceeds tenths of a percent. The morphology of the mineral segregations studied indicates that they are primary and developed during cooling and crystallization of impact melt, accompanied by its separation into immiscible silicate and ore components. Both those melts, while still liquid, moved together, thereby giving the corresponding glasses their characteristic microtextures. Additional aspects of the subject are discussed.